2023
DOI: 10.1007/s00062-023-01284-0
|View full text |Cite
|
Sign up to set email alerts
|

Specialist Perspectives on the Imaging Selection of Large Vessel Occlusion in the Late Window

Abstract: Background The proper imaging modality for use in the selection of patients for endovascular thrombectomy (EVT) presenting in the late window remains controversial, despite current guidelines advocating the use of advanced imaging in this population. We sought to understand if clinicians with different specialty training differ in their approach to patient selection for EVT in the late time window. Methods We conducted an international survey of stroke and neurointerven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Many of these imaging features are not widely used or require expensive software that may not be available at many institutions. 41 , 42 , 43 We have also previously shown that clinical outcomes are no different for patients selected for EVT based on perfusion imaging, magnetic resonance imaging, or computed tomography in routine clinical practice. 29 , 44 That said, fewer than half of the patients in this cohort underwent perfusion imaging, so these metrics were not included in the model.…”
Section: Discussionmentioning
confidence: 94%
“…Many of these imaging features are not widely used or require expensive software that may not be available at many institutions. 41 , 42 , 43 We have also previously shown that clinical outcomes are no different for patients selected for EVT based on perfusion imaging, magnetic resonance imaging, or computed tomography in routine clinical practice. 29 , 44 That said, fewer than half of the patients in this cohort underwent perfusion imaging, so these metrics were not included in the model.…”
Section: Discussionmentioning
confidence: 94%
“…56) However, maximizing the number of patients who can be helped necessitates that we broaden our criteria for interventions and update our guidelines. 56,82) Given the low NNT of EVT in stroke, broadening our criteria may dilute the overall effect of EVT but reach a greater number of patients overall that will benefit. We must also search for optimizing firstpass effect [83][84][85] and adjunctive therapies to help maximize the benefit of EVT.…”
Section: Discussionmentioning
confidence: 99%
“…39 Moreover, specialist perspectives may differ on choice of neuroimaging study in the late window. 40 The Society of Vascular and Interventional Neurology Guidelines state that NCCT can be used to evaluate patients presenting in the late window for EVT treatment as an alternative to CTP or MRI, particularly when access to CTP or MRI is limited. 41 The MR CLEAN LATE randomized trial compared EVTversus medical management for patients presenting between 6 and 24 hours of time last seen well based on NCCT and CTA collateral selection.…”
Section: Neuroimaging Selection In the Late Time Windowmentioning
confidence: 99%